Utilizing Decision-making Task: Students' Mathematical Justification in Collaborative Problem Solving - Namirah Fatmanissa; Tatag Yuli Eko Siswono; Agung Lukito; Ismail (Sociedad Española de Investigación en Educación Matemática, 2024)
Many studies reported the importance of mathematical justification in collaborative problem-solving (CPS). However, not all tasks could stimulate mathematical justification in CPS. This study explores the potential of a decision-making task in facilitating mathematical justification in CPS of a derivative topic. Two groups of 12 graders in Bandung, Indonesia solved a task. The group works were observed, recorded, and the written works were collected. The findings showed that the task encouraged the groups to focus on justifying mathematical claims. Both groups successfully solved the task, yet different mathematical justifications were observed. We discussed the possible roles of the task difficulty and groups' mathematics ability in promoting mathematical justifications. Checking the effectiveness of the task on a larger sample was recommended for further studies.